2015
DOI: 10.1051/epjap/2015150019
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of physical properties of screen printed nanosized ZnO films for optoelectronic applications

Abstract: Abstract. Nanosized ZnO particles derived from chemical co-precipitation route were used for casting ZnO films by screen printing method followed by sintering at two different temperatures. The variation in structural, optical and electrical properties of these films with temperature have been investigated by XRD, SEM, FTIR, Raman, UV-VIS, EPR and four probe analytical techniques. XRD patterns of these films exhibit polycrystalline nature with hexagonal wurtzite structure and SEM images reveal the smooth, dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…All rights reserved a vacancy-rich inner phase may favour the crystallite reorganization into larger grains. Also in our case, it is observed that the dislocation density and strain are increased with the decrease of grain size of CuO, this is because in nano regime surface to volume ratio increases 35 .…”
Section: Accepted Articlesupporting
confidence: 63%
“…All rights reserved a vacancy-rich inner phase may favour the crystallite reorganization into larger grains. Also in our case, it is observed that the dislocation density and strain are increased with the decrease of grain size of CuO, this is because in nano regime surface to volume ratio increases 35 .…”
Section: Accepted Articlesupporting
confidence: 63%
“…Synthesis: Materials used include zinc acetate dehydrate and sodium hydroxide.1.00M NaOH was added to 0.5M zinc acetate dehydrate aqueous solutions dropwise with constant stirring for precipitating zinc oxyhydroxide. The precipitated nanoparticles were filtered, dried at 70 o C and sintered at 450 o C to obtain to oxides of nanoparticles [20]. These nanoparticles were characterized by high resolution XRD, SEM, Energy dispersive X-ray Spectroscopy (EDS), FT Raman and UV-VIS analytical techniques to probe their structure, surface morphology and physical characteristics.…”
Section: Synthesismentioning
confidence: 99%
“…spectroscopy is a very powerful sensitive technique used for the characterization of nature of magnetic impurities/defects and spin dynamics in materials that have paramagnetic defects [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] in nanocrystalline zinc oxide. EPR spectra are scanned by varying the magnetic field at constant microwave frequency (i.e., 9.36 GHz in X-band EPR spectrometer).…”
Section: Epr Analysis Electron Paramagnetic Resonance (Epr)mentioning
confidence: 99%